A novel mutation in the cathepsin C (CTSC) gene in Iranian family with Papillon‐Lefevre syndrome - Mahmoud Ghanei; Mohammad R. Abbaszadegan; Mohammad M. Forghanifard; Azadeh Aarabi; Hamidreza Arab (Wiley, 2021)
Abstract Objectives In this study, we analyzed the whole exomes of CTSC gene in a family with history of PLS. Materials and methods Genomic DNA was extracted from peripheral blood and genotype analysis was performed. The mutated protein sequence was used to find the best possible tertiary structure for homology modeling. The homology modeling of the novel mutation was then performed using the online Swiss‐Prot server. The results were also analyzed for to verify its validity. Results The analysis of CTSC gene elucidated a novel insertion GAC. The novel mutation was proved by analyzing 50 healthy control volunteers. Modeling of the novel found mutation in CTSC gene revealed structural defects that may have caused the functional abnormalities. Conclusions The structural analysis of the mutated protein model identifies changes in the stereo‐chemical and the energy level of the mutated protein. Since this protein play a role in the activation of granule serine proteases from cytotoxic T lymphocytes, natural killer cells, mast cells, such structural defects may lead to its malfunction causing dysfunctioning of immune defense mechanisms.